The Hungarian prison system in the light of AI and smart tools - Orsolya Czenczer; Tamás Hinkel (Revija za kriminologiju i krivično pravo)
Artificial intelligence, or AI, is already present in many areas of our lives, such as medicine, engineering, business, banking, etc., but you only need to reach into your pocket and your phone's virtual assistant is powered by AI. Therefore, we cannot afford to ignore AI, to "ignore it", because it is part of our everyday lives, even if it goes unnoticed, and it is likely to become more and more prevalent in our world in the future, both in our professional and private lives. Hungary is one of the first countries in the world to build a smart prison in Csenger, which will use several types of artificial intelligence. The smart prison being built is a curiosity in the history of the Hungarian penitentiary system, and perhaps we do not even realise how much this innovative technology will take the burden off the shoulders of the staff working in penitentiary institutions. However, we believe that there are many challenges, even risks, that AI could bring (especially in learning to manage it well and to accept it).